(3XGgQGJ Gdadc dEbdjOSs
(3ChdgG (B:s
(3HYO GdOjHGLI KdGKI hYTQhf TcdkG haj HYV GdfSN NeSI hYTQhf TcdkG s
(3BNQgG (B:s
(3aEf ReGf JHOjd cd hGMO efgG fUa GdcQI GdNaj GYXe ef ReGf JHOjd Cj bhS cGfJ ZjQgG ef Pdc GdfUa fUa GdcQI GdXGgQI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B100 - (3U(B118s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdj (B(1930) s
Keywords: (3eJaQbGJs